O planejamento nas práticas gerenciais de um hospital universitário - Souza, Lucinete de Oliveira (2018)
The University Hospitals under the perspectives of management are complex institutions of health that require great support from public funds to be kept running. They have an important role to the development of the National Health Service (SUS) by means of research, production of knowledge, professional healthcare training, and service delivery of high complexity to the population. So, it is important to establish systematized practices of planning and management, aiming the organization and the running of these institutions, in view of the complexity of the activities that they develop and the diversity of professionals involved in the production of health for the effective accomplishment of the mission. Objective: To describe the perception of the managers at a University Hospital about the planning related to management practices and to propose a work with the managers from these hospitals. Methodology: It is a descriptive research with a qualitative approach and the data collection were done through semistructured interviews with 20 people holding management posts designed through Ordinance. The data were submitted to a content analysis of Bardin. Outcomes: the results showed the construction of a category called improvisation because the perception of the managers about the planning is supported by a process of planning and management which is not systematized. There is fragility in the strategic direction system and the managers cannot see the importance of planning. There is a necessity of creating strategies to allow the sensibility and discussion of a planning process among the managers and it was suggested a Product which is an educative material with the structure of a booklet with information about the topic to help the understanding of this subject and to stimulate the applicability.